SİYASAL BÜTÜNLEŞME PROJELERİ VE "DIŞLAYICI SÖYLEM" (SAFLAŞTIRMA ARAYIŞI) GERİLİM HATTINDA AB VE TÜRKİYE ÖRNEĞİ1 - (:unkn) unknown (My University, 2008)
Çoğulcu liberal demokrasileri bir araya getiren "AB bütünleşme projesi"nin "derinleşmesi" ve "genişlemesi" yönünde atılan adımlara karşı, "popülist radikal sağ"ın dışlayıcı "yeni ırkçı" formülü çerçevesinde toparlanan hareketler durmaktadır. Çoğulcu bütünleşme projeleri-dışlayıcı ideolojiler gerilimi incelenirken, dışlayıcı söylemin temellendiği birçok devinim malzemesini Türkiye'nin AB üyeliği hedefine karşıtlık temasıyla kesişme noktasında buluruz. Türkiye karşıtlığı popülist radikal sağın popülerleşme arayışında "Avrupa'lı Avrupa" kurgusu ("Beyaz Avrupa") çağrışımını güçlendirerek, aslında, çoğulcu bir bütünleşme projesi olan AB'yi kökten sarsma potansiyeli taşımaktadır. Sorunu Türkiye - AB ilişkilerine karşıtlıktan çok, AB de (ve Türkiye de) varolan çoğulculuk yanlısı aktörlerle, "dışlayıcı" saflaştırıcı projelerden yana aktörlerin çatışmasıyla, bütünleşme projesini nasıl sürdürebileceklerinde arıyoruz.

Against the "profundity" and "expansion" steps of the EU unification project, which unite pluralist liberal democracies, there are movements assembling around the "new racist" formula of the "radical populist right". In order to study the tensions between pluralist unification projects and exclusionist ideologies, we analyze many of the mobilization targets funding the populist radical right's opposition to Turkey's EU membership objective. On the other side, in Europe, opposition to Turkey's integration is often used to reinforce the populist radical right's concept of "European Europe" construction (or "White Europe"). All those results have a potential of radical harm vis-à-vis EU's pluralist unification project. We focus on the problem of how the unification project may be sustained, namely taking into account the existing struggle between pluralist and exclusionist actors, as well as "purification" tendencies at work both in the EU and in Turkey.
(ON TENSIONS BETWEEN PROJECTS OF POLITICAL UNIFICATION AND "EXCLUSIONIST DISCOURSES" (SEARCH FOR "PURIFICATION") THE CASE OF EU AND TURKEY)
Keywords: Hukuk